2016
DOI: 10.1111/weng.12215
|View full text |Cite
|
Sign up to set email alerts
|

Analysing perceptions of English in rural Bangladesh

Abstract: Drawing on research analysing perceptions of English in rural Bangladesh, the paper explores the ideological and practical issues involved in the promotion of English in this context, with respect to the language's former and current associations with colonial and imperialist agendas, and the politico‐cultural situation of present‐day Bangladeshi society. The analysis – which is underpinned by a blending of world Englishes and postcolonial theory – reveals how dominant discourses of English as a language of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Erling et al ( 2012) carried out a study in two rural areas of Bangladesh, which found positive attitude towards the role of English as a tool of economic development. Seargeant et al (2017) also examined the impact of English-language education on the social, economic and cultural identities and found that "English as a language of global opportunity persists in these rural communities, despite the limited opportunities for using the language or developing proficiency in it" (p. 631).…”
Section: English Education and Socio-economic Development In The Bang...mentioning
confidence: 99%
See 1 more Smart Citation
“…Erling et al ( 2012) carried out a study in two rural areas of Bangladesh, which found positive attitude towards the role of English as a tool of economic development. Seargeant et al (2017) also examined the impact of English-language education on the social, economic and cultural identities and found that "English as a language of global opportunity persists in these rural communities, despite the limited opportunities for using the language or developing proficiency in it" (p. 631).…”
Section: English Education and Socio-economic Development In The Bang...mentioning
confidence: 99%
“…An ethnographic study in EFL or ELT is so rare in Bangladesh that a single and very short ethnographic study of fewer than two weeks, funded by the British Council at the beginning of the 2010s, was used in several publications which were published from 2011 to 2017 by some leading international publishers and top-ranking journals including Springer, Cambridge University Press, Multilingual Matters, Wiley, British Council, UK, etc. (Erling, 2017;Erling, Seargeant, & Solly, 2014;Erling et al, 2012;Hamid & Erling, 2016;Seargeant & Erling, 2011;Seargeant, & Erling, 2013;Seargeant, Erling, Solly, Chowdhury, & Rahman, 2017). As it is tough to carry out ethnographic research in a rural area due to lack of funding, leave from the job, and expertise; the questionnaire-based and interview-based abundant studies are found in ELT and EFL in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh provides a particularly fruitful site of analysis because language planning in this country has been uniquely influenced by colonial histories, national priorities and development initiatives. As explored in depth elsewhere (Hamid & Erling, 2016;Seargeant, Erling, Solly, Chowdhury & Rahman, 2016), the emergence of the country is essentially the result of a language planning problem and the intensity of feeling around the national language is reflected in the name of the country, which literally means 'Country of Bangla'.…”
Section: Context: Language Planning and Development Aid In Bangladeshmentioning
confidence: 99%
“…Finally, a small-scale qualitative study conducted in two rural communities in Bangladesh, conducted independently of EIA, is presented, providing further insight into the needs and perceived value of English at the local level (see further Erling, Seargeant, Solly, Chowdhury & Rahman, 2012;Erling, Seargeant & Solly, 2014;Seargeant et al, 2016).…”
Section: Research Synthesis and Critiquementioning
confidence: 99%
See 1 more Smart Citation